AQUIVION® perfluorosulfonic acid resin for butyl levulinate production from furfuryl alcohol. (23rd August 2019) - Bernal, Hilda Gómez; Oldani, Claudio; Funaioli, Tiziana; Raspolli Galletti, Anna Maria
Abstract : Multivariate analysis allowed the optimization of a reaction catalyzed by a robust solid acid Aquivion® P87S. Abstract : This study reports the sustainable production of butyl levulinate (BL) from furfuryl alcohol (FA), a highly abundant biomass derived platform obtained from C5 sugars in hemicellulose. FA upgrading is performed adopting a robust and easily recyclable commercial perfluorosulfonic acid resin, Aquivion® P87S, used as cylinder shaped pellets. This approach avoids the use of corrosive and harmful mineral acids allowing a simple separation of the catalyst from the reaction mixture, reducing the cost of equipment materials and disposal or neutralization issues, also resulting in reduced solvent dehydration. Moreover, FA alcoholysis to BL involves butanol as a sustainable reaction medium, also readily obtained from biomass. The catalyst remains stable up to 6 recycles. Furthermore, the absence of heavy by-products and the stability of the catalyst allowed us to perform successive additions of the substrate to the reaction medium to increase the BL concentrations up to 0.66 M (13 wt%).